Ontological reconfiguration of management in the face of the emergence of artificial intelligence (Gestión y Gerencia, 2025)
This research analyzes how the emergence of Artificial Intelligence challenges and reconfigures the ontological foundations of managerial function; specifically, it reflects on the irreplaceable value that human managers can continue to contribute within a scenario mediated by intelligent technologies. To address this complex issue, the research is grounded in a critical documentary analysis of recent academic-scientific literature. The results suggest that AI, by optimizing processes, managing large volumes of data, and generating recommendations with high precision, notably increases efficiency and agility in organizational decision-making. Nevertheless, the study simultaneously highlights the persistence and revaluation of irreplaceable human qualities. It is evidenced that critical judgment, ethics, soft skills, as well as intuition, empathetic leadership, and the ability to manage teams under uncertainty constitute the differential value and primacy of the human manager, since AI inherently lacks consciousness and common sense. It is concluded that the managerial role does not become obsolete, but rather transforms and reorients toward a meta-management, with the manager becoming an orchestrator between human and artificial intelligence, enhancing AI's operational performance while simultaneously safeguarding qualitative human interactions and the indispensable social and ethical responsibility in the organizational environment.
Keywords: Artificial intelligence; decision-making; human role; management; transformation